Study on Coulomb Stress Triggering of the April 2015 M7.8 Nepal Earthquake Sequence - Jianchao Wu; Qing Hu; Weijie Li; Dongning Lei (International Journal of Geophysics)
In April 2015, a M7.8 earthquake occurred less than one month before a M7.3 earthquake near Kodari, Nepal. The Nepal earthquake sequences also include four larger (M > 6) aftershocks. To reveal the interrelation between the main shock and the aftershocks, we check the role of coseismic coulomb stress triggering on aftershocks that follow the M7.8 main shock. Based on the focal mechanisms of the aftershocks and source models of the main shock, the coulomb failure stress changes on both of the focal mechanism nodal planes are calculated. In addition, the coulomb stress changes on the focal sources of each aftershock are also calculated. A large proportion of the M > 6 aftershocks occurred in positive coulomb stress areas triggered by the M7.8 main shock. The secondary triggering effect of the M7.3 aftershock is also found in this paper. More specifically, the M7.3 aftershock promoted failure on the rupture plane of the M6.3 aftershock. Therefore, we may conclude that the majority of larger aftershocks, which accumulated positive coulomb stress changes during the sequence, were promoted or triggered by the main shock failure. It suggests that coulomb stress triggering contributed to the evolution of the Nepal M7.8 earthquake sequence.